Effectiveness of positive pressure evaporative cooling on broilers production - Muhieldeen, Osama A.; Abdalla, Abdelhafeez M.; Yousif, Yousif E.; Abdelmutalap, Salah A. (المجلة الزراعية; مجلد 1 عدد 2 (2003), 2021)
The main concept of this research depends on the experimental work being performed on broiler houses, using positive pressure evaporative cooling systems. The experiments were conducted at the farms of the People's Development Company for Animal Production, Wad Medani, Sudan, during the period of May-July 1998. The objective was maintaining better environmental conditions during summer months, i.e., temperature and relative humidity, for housed birds, in order to obtain the maximum rate of birds growth, and reduce the rate of mortality, thus increasing economic returns. To evaluate the performance of broilers production, the parameters studied were temperature and relative humidity for bird's houses, live body weight, feed intake, water intake and mortality rate. The results of the experiments showed that evaporative cooling reduced the temperature by 18.9% and 16.6% in the houses with bird density of 10 birds/m2 and 13 birds/m2, respectively. The live body weight increased by 26.5% and 21.9% in the houses with bird density of 10 birds/m2 and 13 birds/m2, respect- tively. The mortality rate in the same houses was reduced by 79% and 75.7%, respectively. The results indicated that evaporative cooling effect was highly •siY1ificantly and positively correlated with most of the measured triats.